PENGARUH TIME BUDGET PRESSURE (TBP) TERHADAP KUALITAS AUDIT - Umi Khulsum; Tulus Suryanto; Juhary Ali (MANAJEMEN, 2023)
This study aims to determine the effect of Time Budget Pressure (TBP) on audit quality using associative quantitative research methods. The sample consists of external auditors working at Public Accounting Firms (KAP) in the DKI Jakarta area. Data were collected through a survey with an ordinal scale-based questionnaire, and analyzed using statistical methods. The results showed that TBP has a significant positive effect on audit quality, with a T-statistics value of 2.353 and a p-value of 0.019. This finding indicates that TBP, which is optimally implemented, can improve the efficiency and effectiveness of the audit process. Auditors with high skills are able to utilize TBP to prioritize important tasks, increase focus, and find innovative solutions. this study also highlights the potential negative impacts of TBP if time pressure is excessive, such as decreased audit accuracy and depth, and increased stress on auditors. In extreme conditions, TBP can affect communication with clients and the overall quality of audit results. Therefore, a good time management strategy is important to mitigate this risk. This study provides insight into the importance of proper time planning and management to improve audit quality while maintaining auditor work balance.